1967
DOI: 10.1677/joe.0.0390423
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Tissue Distribution of Norethisterone and Norgestrel in Rabbits

Abstract: After injection of [4-14C]norethisterone or norgestrel labelled with 14C in the ethynyl group into rabbits, 45 % and 57\m=.\4% of the radioactivity was excreted in the urine, mostly within 2 days. Although small amounts of radioactivity were excreted in the expired air of rabbits receiving norgestrel, little metabolism of the ethynyl group occurred. Radioactivity in plasma declined quickly after injection and 24 hr. later less than 0\m=.\5 % of the dose remained in the circulation. Up to 5 hr. after injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

1968
1968
1984
1984

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
4
11
0
Order By: Relevance
“…Subject M 3 received 1 pc [14C]norgestrel adsorbed on to lactose in a gelatine capsule orally. The details of the investiga¬ tions together with the methods used for the estimation of radioactivity in urine and blood have been described previously (Kamyab, Littleton & Fotherby, 1967;Kamyab, Fotherby & Klopper, 1968a). For the isolation and identification of norgestrel metabolites, urine from subject M 2 was pooled and extracted in 11. quantities.…”
Section: Methodsmentioning
confidence: 99%
“…Subject M 3 received 1 pc [14C]norgestrel adsorbed on to lactose in a gelatine capsule orally. The details of the investiga¬ tions together with the methods used for the estimation of radioactivity in urine and blood have been described previously (Kamyab, Littleton & Fotherby, 1967;Kamyab, Fotherby & Klopper, 1968a). For the isolation and identification of norgestrel metabolites, urine from subject M 2 was pooled and extracted in 11. quantities.…”
Section: Methodsmentioning
confidence: 99%
“…When the bile duct of the animal was cannulated urinary excretion was reduced and 26-41% of the dose was found in bile. Using norethisterone or norgestrel, Kamyab et al (1967) found about half of the dose was excreted in the urine during a 7 day period with up to 5 % in the faeces. Some of the dose was excreted rapidly, as much as one quarter being found in the urine of some animals within 4 to 5 h of injection.…”
Section: In Vivo Metabolism Of Synthetic Progestogensmentioning
confidence: 99%
“…Studies on the metabolism of these compounds in women have demon¬ strated that the ethynyl group in norethindrone remains intact (Kamyab, Fotherby & Littleton, 1967 ; Kamyab, Fotherby & Klopper, 1968 ;Fotherby, 1974), but that the ring A is transformed into several reduced products, i.e. 17rz-ethynyl-17ß-hydroxy-5a-oestran-3-one and 17ct-ethynyl-5a-oestrane-3ß,17ß-diol (Murata, 1968), 17o>ethynyl-5a-oestrane-3a,17ß-diol and 17a-ethynyl-5ß-oestrane3a,17ß-diol (Gerhards, Hecker, Hitze, Nieuweboer & Bellmann, 1971 ; Stillwell, Horning, Horning, Stillwell & Zlatkis, 1972).…”
Section: Introductionmentioning
confidence: 99%